Cut! that’s a wrap: regulating negative emotion by ending emotion-eliciting situations - Vujovic, Lara; Opitz, Philipp C.; Birk, Jeffrey L.; Urry, Heather L. (Frontiers in Psychology, 2014)
Little is known about the potentially powerful set of emotion regulation (ER) processes that target emotion-eliciting situations. We thus studied the decision to end emotion-eliciting situations in the laboratory. We hypothesized that people would try to end negative situations more frequently than neutral situations to regulate distress. In addition, motivated by the Selection, Optimization, and Compensation with Emotion Regulation framework, we hypothesized that failed attempts to end the situation would prompt either a) greater negative emotion or b) compensatory use of a different ER process, attentional deployment (AD). Fifty-eight participants (18-26 years old, 67% women) viewed negative and neutral pictures and pressed a key whenever they wished to stop viewing them. After key press, the picture disappeared (‘success’) or stayed (‘failure’) on screen. To index emotion, we measured corrugator and electrodermal activity, heart rate, and self-reported arousal. To index overt AD, we measured eye gaze. As their reason for ending the situation, participants more frequently reported being upset by high- than low-arousal negative pictures; they more frequently reported being bored by low- than high-arousal neutral pictures. Nevertheless, participants’ negative emotional responding did not increase in the context of ER failure nor did they use overt AD as a compensatory ER strategy. We conclude that situation-targeted ER processes are used to regulate emotional responses to high-arousal negative and low-arousal neutral situations; ER processes other than overt AD may be used to compensate for ER failure in this context.